1977
DOI: 10.1111/j.1151-2916.1977.tb15484.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grinding on Flaw Geometry and Fracture of Glass

Abstract: Fracture mechanics is combined with fracture surface analysis to analyze brittle failure of glass bars which were tested relative to the direction of grinding. Grinding essentially produces two sets of flaws from which failure occurs. In the most severe set, formed basically parallel to the grinding direction, the ratio of the average depth (a) to the half‐width (b) is 0.5. In the less severe set, formed perpendicular to the grinding direction, the average a/b ratio is 1.6. In both sets the most severe flaws a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(37 citation statements)
references
References 4 publications
1
35
0
1
Order By: Relevance
“…The rate of SCG is a power law function of stress intensity factor [9]. The shapes of the flaws within the material affect the stress intensity factor such that sharp flaws and flaws with high depthto-width ratios correspond to greater stress intensity factor at the same stress level and hence faster SCG than blunt flaws and flaws with low depth-to-width ratios [13]. Additionally, the presence of moisture usually has a deleterious effect [14].…”
Section: Introductionmentioning
confidence: 99%
“…The rate of SCG is a power law function of stress intensity factor [9]. The shapes of the flaws within the material affect the stress intensity factor such that sharp flaws and flaws with high depthto-width ratios correspond to greater stress intensity factor at the same stress level and hence faster SCG than blunt flaws and flaws with low depth-to-width ratios [13]. Additionally, the presence of moisture usually has a deleterious effect [14].…”
Section: Introductionmentioning
confidence: 99%
“…al. 16 showed that grinding introduces two types of microcracks: one which is parallel to the grinding direction and one which is perpendicular to the grinding direction. The parallel microcracks are typically more severe.…”
Section: Discussionmentioning
confidence: 99%
“…Other sources discuss the existence of machining-induced flaws that have been studied using fractographic observations [26,22]. Similarly the failure origins were associated with machining damage [27] and grinding-induced cracks [28,29].…”
Section: Machining Flawsmentioning
confidence: 99%
“…Machining strongly influences the configuration of the entire edge flaw population, and thus the final strength of a bended specimen [22].…”
Section: Machining Flawsmentioning
confidence: 99%